Endogenous product adjustment and exchange rate pass-through - Andreas Freitag; Sarah Lein (University of Basel, Center of Business and Economics (WWZ), 2022)
We document how product quality responds to exchange rate movements and quantify the extent to which these quality changes affect the aggregate pass-through into export prices. We analyze the substantial sudden appreciation of the Swiss franc post removal of the 1.20-CHF-per-euro lower bound in 2015 using export data representing a large share of the universe of goods exports from Switzerland. We find that firms upgrade the quality of their products after the appreciation. Furthermore, they disproportionately remove lower-quality products from their product ranges. This quality upgrading and quality sorting effect accounts for a substantial share of the total pass-through one year after the appreciation. We cross-check our results with the microdata underlying the Swiss export price index, which includes an adjustment factor for quality based on firms' reported product replacements, and obtain similar results.
Keywords: E3; E31; E50; F14; F41; 330; large exchange rate shocks; exchange rate pass-through; quality adjustment